Genetically modified organisms in agriculture : economics and politics - Nelson, Gerald C. (Academic, 2001)
Genetically modified crops have become a topic of great interest among scientists, regulators, consumers, farmers, and politicians. Despite their potential benefits, public hostility toward these crops is causing dramatic changes to import/export policies, food safety regulations, and agricultural practices around the world. Genetically Modified Organisms in Agriculture provides a comprehensive overview of the subject and a balanced look at the costs and benefits of GMO products.Part I reviews the scientific, economic, and political issues relating to the use of agricultural GMOs. Chapters cover specific applications, regulatory concerns, import/export patterns, international trade issues, and a discussion of future trends. Part II offers a unique look at all sides of the GMO controversies, with short chapters contributed by leading individuals with widely different perspectives. Part III presents a more in-depth look at selected issues plus helpful reference materials.This book makes the latest information on GMOs accessible to all interested parties, including students, laypeople, scientists, activists, and professionals working in related fields. * Additional detailed footnotes and references for the academic* International contributions from the US, Europe and India* Covers the perspectives of different groups involved in the controversies: governments, environmental agencies, consumers, industrial agencies and the developing world